Quality and Antioxidant Activity of Arrowroot (Maranta arundinaceae L.) Tuber Accessions Collected from Java Island - Zuraida Sagala; Dyah Iswantini Pradono; Sulitijorini Sulitijorini; Triadiati Triadiati (Institut Pertanian Bogor, 2025)
Arrowroot (Maranta arundinaceae L.) is a starch–producing plant that can potentially be used as an alternative substitute for wheat flour. Additionally, arrowroot can serve as a functional food, as it is not only a source of nutrition but also provides health benefits such as improving digestion and regulating blood sugar levels. Arrowroot tubers contain high levels of carbohydrates and bioactive phenolic compounds that function as antioxidants. Currently, no data is available on the nutritional content and antioxidant activity (DPPH assay) of arrowroot tubers from various regions of Java Island. This study aimed to analyze the quality and antioxidant activity of arrowroot tubers obtained from several locations in Java. The results of the proximate analysis (moisture and ash contents) showed that the lowest moisture content was in the Banjar 1 accession (3.44%), while the highest was in the Sragen 3 accession (12.47%). The Banjar 2 accession had the highest ash content (8.94%), while the Sragen1 accession had the lowest (3.98%). The antioxidant activity was indicated by the IC50 value, which is the concentration of the sample solution required to inhibit 50% of DPPH free radicals. Antioxidant activity analysis revealed that the Malang 1 accession had the lowest IC50 value of 163.16 ppm, indicating the highest antioxidant potential. Keywords: 1,1–diphenyl–2–picrylhydrazyl, antioxidant, arrowroot, phenol, phytochemicals